An integrated instrumental and sensory techniques for assessing liking, softness and emotional related of gluten-free bread based on blended rice and bean flour - Aguiar, Etiene V.; Santos, Fernanda G.; Faggian, Letícia; da Silveira Araujo, Marielle Batista; Araújo, Vitória Alves; Conti, Ana Carolina [UNESP]; Capriles, Vanessa D. (Elsevier, 2022)
Despite recent scientific advances and the growth of the gluten-free market, important issues such as the improvement of the sensory and nutritional quality of gluten-free bread (GFB) still need to be addressed. Therefore, the aim of the present study was to integrate instrumental and sensory techniques for assessing liking, softness, and emotions related to GFB based on rice flour (RF) and bean flour (BF). Results shows that common BF increases the ash, protein, and dietary fiber content of bread. The RF and BF blend improves dough thermomechanical properties, bread volume, instrumental texture properties and acceptability, as well as being the formulation indicated by consumers as presenting ideal softness, all of which subsequently correlated with positive food-related emotions, based on a facial emojis list. Thus, a RF and BF blend is a valuable ingredient producing nutrient-dense and acceptable GFB, which is important for consumers who choose or must adhere to a gluten-free diet. This research highlights promising predictors able to correlate dough parameters, as well as physical properties of bread with the sensory quality of GFB; this could be helpful to food scientists and producers to conduct extensive sensory and consumer research regarding both commercial and experimental GFB to establish whether those products meet consumer expectations, showing the relevance of continuing studies.
Keywords: Acceptability; Face emojis; Food texture; Food-related emotions; Gluten-free; Just-About-Right; Mixolab